Socialization and Guidance on Filing Annual PPh 21 Tax Returns at Universitas Islam Lamongan in 2024 - Satiti, Abidah Dwi Rahmi; Kurniyawati, Indah; Aini, Ade Nur; Iskandar, Mahani Jhonata (Proceeding of International Management Conference and Progressive Papers, 2025)
Taxpayers often perceive the e-filing policy as imposing an excessive tax burden. Difficulties in completing the e-filing process may contribute to low levels of tax compliance in reporting and paying taxes. This community service program aims to enhance tax knowledge and awareness among the academic community of Universitas Islam Lamonganth rough socialization and technical assistance on the reporting of Annual PPh 21 Tax Returns. The methods employed in this program include observation, questionnaire distribution, and hands-on technical assistance to ensure participants’ understanding of the tax reporting process, focus group discussion and evaluation. The results indicate that most lecturers and administrative staff initially lacked understanding of how to complete Annual PPh 21 Tax Returns through the e-filing system. However, a significant improvement in participants’ comprehension was observed after their involvement in this activity. This community service initiative contributes to supporting government efforts in disseminating tax regulations, increasing taxpayer compliance, and assisting the public in the proper reporting of Annual PPh 21 Tax Returns. Keywords: annual PPh 21 tax returns, socialization, guidance, e-filing